(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Nanotechnology is projected the engineering of functional systems at the molecular scale. In its true sense, ’nanotechnology’ is considered as ability to construct items from the bottom up approach, using techniques and tools being developed day to day to make complete products of high performance. CNTs due to their extra ordinary properties and applications are considered as one of the high performance Nano material. Considering the importance of CNTs as Nano material a green route is developed to produce them using protein and metal salt solution. The CNTs and protein metal complex are characterized using NMR, UV, XRD and TEM.